First Human Case of Metacestode Infection Caused by Versteria sp. in a Kidney Transplant Recipient. (13th September 2018) - Barkati, Sapha; Gottstein, Bruno; Müller, Norbert; Sheitoyan-Pesant, Caroline; Metrakos, Peter; Chen, Tianyan; Garceau, Richard; Libman, Michael D; Ndao, Momar; Yansouni, Cedric P
Abstract: Cestodes are emerging agents of severe opportunistic infections among immunocompromised patients. We describe the first case of human infection, with the recently-proposed genus Versteria causing an invasive, tumor-like hepatic infection with regional and distant extension in a 53-year-old female kidney transplant recipient from Atlantic Canada.